The analysis of influence of accuracy of synchronization on a noise stability of reception MSK of signals - Паук, С. М.; Потапов, В. Г.; Тараненко, А. Г.; Ткалич, О. П. (Problems of Informatization and Control, 2009)
The Organized estimation of the influence to accuracy to synchronizing on noise-immunity communications network with frequency inflexion (MSK). The Noted advantage MSK signal. The Analysed inexactnesses to synchronizing on radio frequency and on pulsing pulse on noise-immunity MSK signal. The Certain level dеsynchronization for MSK signal on pulsing pulse and on radio frequency